SURVEI PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN PADA SATUAN PENDIDIKAN SD, SMP, SMA NEGERI SE-KECAMATAN KARANGAN KABUPATEN TRENGGALEK - HADI, SOFYAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The improvement of sport, physical and health education at school has important role student’s means, beside it develop students achievement especially at physical education. To realize this condition, there are several thing required by student. Those are proper infrastructure, competent teacher, teacher’s work, also achievement and award got by teacher and student. There was renewable Pangkalan Data Pendidikan Jasmani dan Olahraga Indonesia (PDPJOI) on april 2nd 2011. Therefore, the researcher would like to know the condition of physical education in karangan subdistrict, because in karangan subdistrict, there is no research that conducted about the condition of physical education yet. Statement of problem in this research are : (1)how is the condition of sport and physical education at public elementary school around karangan subdistrict in years 2012/2013  (2) how is the condition of sport and physical education at public junior high school around karangan subdistrict in years 2012/2013  (3) how is the condition of sport and physical education at public around karangan subdistrict in years 2012/2013? In this research, the researcher used the instrument of PDPJOI that includes four aspects. They are (1) the availability of facilities and infrastructure  (2) the existence of physical education teacher (3) the overall result of educational unit’s work in year 2012  (4) achievement and award in year 2012. The result of recapitulation data in public elementary school ,junior high school and senior high school are  (1) the average score of public elementary school 598 was categorized “ C ”  (2) the average score of public junior high school 677 was categorized “ B ”  (3) the average score of public senior high school 755 was categorized “ B ”. The conclution is the condition of sport and physical education in educational unit of public elementary school, junior high school and senior high school got the score 615,81 and was categorized “ B “. The school that got the highest score is SDN 1 Buluagung, SMPN 1 Karangan, and SMAN 2 Karangan. Most of educational unit at Karangan subdistrict, their sport and physical education had subjectively develop. Keyword :  Progress of physical and health education unit of public lementary school, junior high school and senior  high school.